LEXICAL AND STYLISTIC FEATURES OF FASHION DISCOURSE IN ENGLISH MAGAZINE ARTICLES (SCIENCE TIME JOURNAL, 2026)
This article explores the lexical and stylistic features of fashion discourse in English magazine articles. The study focuses on identifying specific linguistic elements characteristic of fashion texts, including terminology, neologisms, metaphorical expressions, and stylistic devices typical of advertising language. Special attention is given to the use of expressive and evaluative language that enhances emotional impact and reader engagement. Furthermore, the communicative and pragmatic aspects of fashion discourse are examined to reveal how language influences readers’ perceptions and attitudes. The findings contribute to a deeper understanding of the linguistic nature of fashion discourse and its functional role in modern media.